EVALUATION OF OXIDATIVE STRESS, ANTIOXIDANT DEFENSES, AND BIOCHEMICAL DYSREGULATION IN OBESE VS. NON-OBESE ADULT MALES - Adil, Sozdar A; Mohammed, Lina Y (Science Journal of University of Zakho, 2025)
Obesity is a major public health concern linked to metabolic disturbances and increased oxidative stress. The objective of this research is to evaluate the effect of obesity on oxidative–antioxidant balance in adult males. Comparative cross-sectional study was done at Zakho General Hospital, Iraq, from October 2024 to January 2025, involving 90 males aged 18–44 years, distributed into obese body mass index (BMI) ≥30 and non-obese body mass index (BMI)
Keywords: Obesity; Oxidative Stress; Antioxidants; Trace Elements; Metabolic Parameters